Role of formal ontologies in modern information system engineering - Čiukšys, Donatas; Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2003)
Paper discusses the importance of role formal ontologies play in information system engineering, analyses different conceptions of formal ontology, analyses relations of conceptualization, ontology and domain theory, gives formal definition of conceptualization as intensional semantic structure. Definition of formal ontology, acceptable in field of information system engineering, is proposed.